HUBUNGAN KARAKTERISTIK SANTRI DENGAN PERSEPSI MEREKA TENTANG KEMANDIRIAN DI PONDOK PESANTREN - Dwi Purwoko; Amri Jahi; Pang S. Asngari; Darwis S. Gani; M. Hisyam (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2007)
The study analyzed the student’s perceptions self autonomi in islamic boarding school. The research aims were (1) to describe santri distribution at spesific observed characteristic, (2) to decsribe santri perception concerning independency, (3) to describe existence of relation between perceptions with several of santri characteristics. The santri included in this research were 487 persons those located around Pesantren in Jakarta, West Java, Central Java, and East Java. There were 13 santri characteristics analyzed in the study: Type of Pesantren, Santri Age, Sex, Duration of Schooling in Pesantren, Santri’s Family Background, motivation, intensity in reading books, intensity in interacting with teachers (known as “Kyai”), tribe, distance and condition of pesantren, education background before enrolling, and origin. Independent variables related to the indicators of self autonomy included religion, general knowledge, hope for future, social interaction, discussion in the class, personal management, tolerance, and behavior against the government. Corelation analysis is done by using concordance Kendall W and Kendall Tau showed all of santri characteristics existence of high level agreement in evaluating the independency field.